DISTALLY BASED SUPERFICIAL SURAL ARTERY FLAP FOR FOOT AND ANKLE RECONSTRUCTION IN CHILDREN - Mahmood, Farrukh; Mehrose, Muhammad Younas; Tasneem, Shehzadi; Mahmood, Nasir; Raza, Ahmad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Wheel spoke injury of the ankle and foot is very common in children and its reconstruction is challenging. Reverse sural artery flap is very useful to cover these defects. Free tissue transfer is an option in children which needs a micro-vascular expertise, expensive equipment and long operating time. Methods: Sixteen cases with ankle and foot defects were operated during a period of 18 months at the Children Hospital and Institute of Child Health Lahore. The efficacy of sural artery flap for the coverage of these defects was evaluated. Results: Sixteen children presented with defects of foot and ankle, 62.5% were male and 37.5% were female. Their age ranged from 2-13 years. All patients had trauma to the foot, most of them having wheel spoke injury. Some had roadside accidents and glass injury. Fascio-cutaneous flaps were used in 9 patients and fascia only flap in 7 patients with split thickness skin graft. Flaps were used to cover tendoachilles, malleoli, dorsum of foot, calcaneus, amputation stump and to reconstruct heel. Fifteen flaps survived whereas one necrosed. There was loss of skin graft in two cases of adipofascial flaps. Mean follow-up was 6 months. Conclusion: Sural artery flap is quick and safe with wide arc of rotation and minimal donor site morbidity and it does not sacrifice major extremity vessel. Keywords: Superficial sural artery flap, reconstruction, foot and ankle trauma, wheel-spoke injury